Sickness behaviour is induced by a peripheral CXC-chemokine also expressed in multiple sclerosis and EAE. - Campbell, S; Meier, U; Mardiguian, S; Jiang, Y; Littleton, E; Bristow, A; Relton, J; Connor, T; Anthony, D (2010)
Non-CNS chemokine production may contribute to previously unrecognised components of Multiple Sclerosis (MS) pathology. Here we show that IL-8, a neutrophil chemoattractant, is significantly increased in serum from individuals with MS, and that the rodent homolog of IL-8 (CXCL1) is expressed in the liver in experimental autoimmune encephalomyelitis (EAE), a rodent model of MS. The hepatic expression of CXCL1 in EAE is accompanied by neutrophil recruitment to the liver, and we show that this recruitment is a feature of post mortem liver tissue from MS patients, which is a previously unrecognised phenomenon. We speculated that the presence of peripheral CXC-chemokine expression might contribute to the sickness behaviours associated with MS, which are a significant contributor to morbidity. Peripheral, but not central, administration of CXCL1 to Wistar rats inhibited spontaneous activity in the open field and burrowing behaviour in a dose-dependent manner (5-45 microg). The expression of CXCL1 by the liver and the recruitment of neutrophils can be modelled by the intracerebral injection of IL-1beta. Here, we found that interferon-beta (IFN-beta) pretreatment significantly inhibited hepatic CXCL1 production and neutrophil recruitment to the liver induced by the microinjection of IL-1beta into the brain. Thus while the mechanism by which IFN-beta therapy suppresses disease in MS remains unclear, the data presented here suggests that the inhibition of hepatic chemokine synthesis may be a contributing factor.